An Analysis on Some Applications and Theoretical Concept of Operation Research: Exploring the Applications and Concepts of Operation Research in a Competitive Business Environment (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In a competitive business environment, it has become essential for the prosperity and growth in the field of Operation Research. The growing importance of new techniques has been emphasized the need for the developing operation to research models to provide practical utility. These Operation Research models which constitute the subject matters to develop in readers an understanding of problem solving methods. O.R. might be seen as a scientific approach to taking care of problems it abstracts the fundamental components of the problem into a model, which is then broke down to yield an ideal solution for execution. The mathematical points of interest and the explicit techniques used to manufacture and investigate these models can be very modern and are tended to.